TRANSFORMATION OF NURSE PRACTICE AND NURSING EDUCATION: TRENDS, CHALLENGES AND OPPORTUNITIES - FILIPIUK , Dmytro; SMORSHCHOK, Rostyslav (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2025)
Healthcare is undergoing a profound transformation due to a combination of factors that have significantly increased the demand for nursing services. The article examines the dynamic trends shaping the nursing career, identifies the challenges faced by nurses in the changing healthcare environment, highlights the opportunities for nursing education and professional development, and the global impact of knowledge sharing in this profession. The main trends of the future in nursing are outlined: telemedicine revolutionizes patient care; artificial intelligence-based healthcare; data analysis and informatics in nursing; integration of holistic care and personalized medicine; cultural and communication competence. In summary, the future of nursing is marked by several key points: nurses play an important role in patient care, advocacy and education; nursing through increased specialization, integration of technology and greater emphasis on patient-centered care; nurses address the challenges of an aging population, workforce shortages and infectious disease outbreaks; the future of nursing depends on collaboration, knowledge sharing and best practices among nurses around the world. Taking into account the development trends and challenges for nursing identified in the article, future trends are considered: systematic updating of curricula based on new healthcare challenges ˗˗ pandemics and health crises; formation of competencies in innovative areas (informatics, telemedicine); active use of simulation, realistic clinical scenarios in a safe environment; online learning and virtual classrooms; popularization of mentoring programs. It has been established that nursing education is constantly changing. Didactic methods used in other fields can be useful in bridging the gap between theoretical learning and the reality of practical nursing. The quality of nursing education affects nurses' ability to care for patients and use advanced technologies, which contributes to teamwork efficiency, understanding of health policy, ability to analyze information to make critical decisions, and ensuring equity in health care.